The Effect of Entrepreneurial Orientation and Market Orientation on Competitive Advantage at Culinary SMEs in West Sumatera - Yuza, Geby Fadilla; Syafrizal; Yeni, Yulia Hendri (SAFE-Network, 2023)
Competition in MSMEs, especially culinary, makes business people see what factors influence competitive advantage. This study aims to analyze the RBV theory, Entrepreneurial Orientation, Market Orientation and Competitive Advantage at Culinary SMEs in West Sumatra. The population taken in this study are Culinary SMEs in West Sumatra. The sampling method used is non-probability side by using purposive sampling technique. The number of samples in the study was 165. Testing the hypothesis using analysis with two tailed. The data analysis technique is SEM (Structural Equation Model) with the SmartPLS 4 professional application program. The results of study are that entrepreneurial orientation has a positive effect on competitive advantage in culinary SMEs in West Sumatra. Entrepreneurial orientation has a positive effect on market orientation in culinary SMEs in West Sumatra. Market orientation towards culinary competitive advantage in West Sumatra. Market orientation mediates entrepreneurial orientation to competitive effects on culinary SMEs in West Sumatra.